Bloodless Repair of Isolated Pulmonary Artery in a Neonate. (January 2016) - Wang, Hanjay; Brewer, Michael P.; Lai, Wyman W.; Krishnamurthy, Ganga; Chai, Paul J.
Pediatric cardiac surgery, especially for small neonates, typically requires blood products to counter hemodilution during cardiopulmonary bypass. Children with congenital heart defects whose families adhere to faith-based proscriptions against blood transfusion therefore represent a challenging surgical population. Here, we report the case of a ten-day-old, 3.6-kg patient of Jehovah's Witness faith, who was diagnosed with unilateral pulmonary artery discontinuity, bilateral patent ductus arteriosus, and an otherwise structurally normal heart. Pulmonary artery reimplantation was successfully performed without giving blood products. This case adds to previous reports of successful bloodless cardiac surgery in neonates and describes the specific strategies that contributed to successful pulmonary artery reimplantation.